2016
DOI: 10.1093/nar/gkw1302
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional ParF meshwork assembles through the nucleoid to mediate plasmid segregation

Abstract: Genome segregation is a fundamental step in the life cycle of every cell. Most bacteria rely on dedicated DNA partition proteins to actively segregate chromosomes and low copy-number plasmids. Here, by employing super resolution microscopy, we establish that the ParF DNA partition protein of the ParA family assembles into a three-dimensional meshwork that uses the nucleoid as a scaffold and periodically shuttles between its poles. Whereas ParF specifies the territory for plasmid trafficking, the ParG partner p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 50 publications
7
43
0
Order By: Relevance
“…The bacterial TP228 ParA-GFP fusion protein was used as a control and, as previously reported, localized with the E. coli chromosome (Supplemental Fig. S5; Ringgaard et al 2009;McLeod et al 2016). Colocalization was also revealed between wild-type archaeal pNOB8 ParA-GFP and the bacterial nucleoid (Fig.…”
Section: Resultssupporting
confidence: 54%
“…The bacterial TP228 ParA-GFP fusion protein was used as a control and, as previously reported, localized with the E. coli chromosome (Supplemental Fig. S5; Ringgaard et al 2009;McLeod et al 2016). Colocalization was also revealed between wild-type archaeal pNOB8 ParA-GFP and the bacterial nucleoid (Fig.…”
Section: Resultssupporting
confidence: 54%
“…Recent 3D-SIM and single-particle tracking PALM imaging indicated that ParA F does not form filaments in vivo but follows two distinct behaviors: it appears as a few concentrated patches bound to some dense regions of the nucleoid, and it oscillates within the nucleoid (22). Current subcellular imaging supports biochemical data that Brownian ratchet mechanisms (described below) explain dynamic ParA localization and activity in partition (20,22,23,(39)(40)(41)(42)(43).…”
Section: Imaging Plasmids With Type I Partition Systemssupporting
confidence: 55%
“…They have also allowed visualization of plasmid and protein dynamics with high temporal resolution (for review on fluorescence imaging techniques, see reference 17). In addition, evidence indicates that the bacterial chromosome compacted in the nucleoid contributes both passively (as the major structure occupying space inside a bacterial cell) and actively (as a support and/or matrix for plasmid movement) to plasmid partition mechanisms (18)(19)(20)(21)(22)(23); also see below).…”
Section: Visualization Of Plasmid Dynamics In Cellsmentioning
confidence: 99%
See 2 more Smart Citations